The encyclopedia of warfare - Uttridge, Sarah; Catton, Charles (Amber Books, 2014)
Since war is among the oldest of human activities - long antedating the invention of writing - presumably the earliest attempts to record it took the form of poems or songs that were performed on suitable occasions. However revealing or inspiring, poems are no substitute for military theory and written history